The impact of user generated content restaurant websites - Hadamitzki, Cyrielle (2017)
Engaging with users remain something confusing for some marketers. How to effectively taking advantage of content marketing and active networks should be a matter of any organization who is willing to make its business growing. User generated content (UGC), is now everywhere. Less and less consumers purchase goods and services without making a quick research online to make sure they will make their money’s worth. (Mitic, 2016) The increasing popularity of UGC brought me to investigate further in this area of online marketing. Although some practitioners already wrote about the concept of electronic word of mouth (eWOM), not much research has been carried out on decision making based on UGC in the restaurant industry, nor on the impact it engenders for restaurant businesses. Online trends such as UGC are interesting to study because they are changing the marketing landscape and now make the audience more and more reachable. In the restaurant industry especially, it is interesting to see how restaurant establishments integrate these tendencies in their business. The practice of using the Internet as an external source to reach information, is ostensibly not new. However, it has only been a few years that people are getting more and more involved in using reviews platforms when deciding where they want to go eating out. I thus realised that this relatively new consumer behaviour related to restaurant experience deserved to be investigated in. Conjointly, the purpose of this research will be to understand to what extent UGC restaurant websites can impact on both a consumer and a restaurant manager perspective.